HUMANIZATION OF HIGHER EDUCATION OF UKRAINE IN CONTEXT CIVIC EDUCATION - K.Yu. Bogomaz; K.M. Gevel (Academy of Cognitive and Natural Sciences, 2008)
In the article the importance of process of civil education of the young generation is considered for alteration of the democratic legal state. The basic tasks of humanism education of students of higher educational establishments are considered and importance of humanism orientation of educational process is marked. Civil education, education, humanism, culture, humanism education, selfeducation, national self-determination, tehnocratizm, continuous education.